Contemporary Mathematics Learning: Instagram-based math learning medium increased elementary school students' math literacy - Darmawati, Besse; Darmayanti, Rani; Santiago, Paulo Vitor da Silva (Journal of Teaching and Learning Mathematics, 2024)
Modern education has shifted from teacher-centred to student-centred. This transition occurs because educators today work as instructional designers, facilitators, trainers, and learning administrators. Globalization and millennial students are destroying traditional schooling. Technology use is rising. This has adverse effects since youngsters are unwilling to utilize books to improve their mathematical literacy. This happens when pupils need help conceiving, applying, and comprehending mathematical concepts. To improve students' mathematical literacy, a teacher must create modern materials. This study is about R&D. This research produced a math learning tool for 12th-graders. The software emphasizes three-dimensional materials and is based on GeoGebra and Instagram. This study uses the Four-D development model: definition, design, development, and deployment. Modern three-dimensional educational materials made with Canva are the results of this research study. These contents will then be posted on Instagram. This essay will comprehensively analyze data collection, analysis, and Instagram content publishing. Currently, this research is in development, not distribution. Test sheets and questionnaires are used. Observation, interviews, questionnaires, and testing collect data. After observation and interviews, a questionnaire is distributed to finish the study. Pre- and post-tests assessed how GeoGebra Instagram content affected students' understanding of "point-to-point distance" in three-dimensional material. The article will detail this media's methods and results.